Effects of lipoic acid supplementation on rat brain tissue: An FTIR spectroscopic and neural network study - Akkas, S. B.; Severcan, M.; Yilmaz, O.; Severcan, F. (Elsevier Sci Ltd, 2007)
The unfortunate increase in exposure to free radicals justifies antioxidant supplementation. Therefore, in the current study, the effect of exogenously administered lipoic acid, a natural amphipathic antioxidant, on rat brain tissue was investigated via Fourier transform infrared spectroscopy in order to understand its interactions with biological molecules. The results suggest that lipoic acid slightly disorders the acyl chains of phospholipids as observed from the frequency of the CH, stretching vibrations while it strengthens the hydrogen bonding of the interfacial region of phospholipids as indicated by the C=O stretching band. Moreover, lipoic acid seems to cause an increase in the quantity of proteins, without affecting the protein secondary structure revealed by neural network predictions based on FTIR data. These slight variations in the lipid structure and the unaltered protein secondary structure may suggest that lipoic acid is non-toxic and thus support the usage of lipoic acid as an antioxidant supplement. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: lipoic acid; brain tissue; FTIR spectroscopy; lipid order/disorder; hydrogen bonding; neural networks; protein secondary structure